Numerical modelling of iron-pnictide bulk superconductor magnetization. (5th September 2017) - Ainslie, Mark D; Yamamoto, Akiyasu; Fujishiro, Hiroyuki; Weiss, Jeremy D; Hellstrom, Eric E
Abstract: Iron-based superconductors exhibit a number of properties attractive for applications, including low anisotropy, high upper critical magnetic fields ( H c2 ) in excess of 90 T and intrinsic critical current densities above 1 MA cm −2 (0 T, 4.2 K). It was shown recently that bulk iron-pnictide superconducting magnets capable of trapping over 1 T (5 K) and 0.5 T (20 K) can be fabricated with fine-grain polycrystalline Ba0.6 K0.4 Fe2 As2 (Ba122). These Ba122 magnets were processed by a scalable, versatile and low-cost method using common industrial ceramic processing techniques. In this paper, a standard numerical modelling technique, based on a 2D axisymmetric finite-element model implementing the H -formulation, is used to investigate the magnetisation properties of such iron-pnictide bulk superconductors. Using the measured J c ( B, T ) characteristics of a small specimen taken from a bulk Ba122 sample, experimentally measured trapped fields are reproduced well for a single bulk, as well as a stack of bulks. Additionally, the influence of the geometric dimensions (thickness and diameter) on the trapped field is analysed, with a view of fabricating larger samples to increase the magnetic field available from such trapped field magnets. It is shown that, with current state-of-the-art superconducting properties, surface trapped fields >2 T could readily be achieved at 5 K (and >1 T at 20 K) with a sample of diameter 50 mm. Finally, an aspect ratio of between 1 and 1.5 for R / H (radius/thickness) would be an appropriate compromise between the accessible, surface trapped field and volume of superconducting material for bulk Ba122 magnets.